Inculcating social activism in the literature classroom - Ruzy Suliza Hashim, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
Literature has always been one of the vehicles used to promote transformations. Malaysian writer Pak Sako wrote Putera Gunung Tahan to provoke change in the Malay mindset about colonial power. Jose Rizal’s Noli Me Tangere and El Filibusterismo made shattering impact on the Filipino society which now regards the writer as a national hero. Pramoedya Ananta Toer was jailed for what he wrote. These writers are amongst many writers who have made use of their writing dexterity to reveal social ills and effect change for the better. They wrote to describe social conditions, economic development, war and peace, and human development or lack of progress. In this paper, the link between literature and social activism will be discussed and reviewed. Social activism can be defined as attitudes and actions that challenge to persuade the social delivery of status, power, and resources. While the literature classroom should not turn students into agitators without a cause, the choice of texts and the way of teaching can sensitise students to value social activism and engage in pertinent issues that will help them develop not only their critical and analytical skills as students of literature but to imbibe change within themselves and the community.